Detection of Antibody to Burkholderia pseudomallei in Captive and Wild Macaquesin West Java and Bali, Indonesia - VINCENTIUS ARCA TESTAMENTI; DIAH ISKANDRIATI; ARIS TRI WAHYUDI; JOKO PAMUNGKAS (Indonesian Society for microbiology, 2018)
Melioidosis is an emerging zoonotic disease caused by the saprophytic Burkholderia pseudomallei, which infects human and a wide range of animal species. Melioidosis may lead to septicemia and pneumonia in human patients, which can be fatal if the patient is not treated accordingly. The disease is spread in tropical areas and is highly endemic to Southeast Asia and Northern Australia. However, melioidosis is poorly reported in Indonesia, especially in the veterinary field. This research provides serological evidence of antibodies to B. pseudomallei in both captive and wild nonhuman primates. Plasma samples were taken from a total of 390 monkeys in captivities and wild habitats in West Java and Bali, Indonesia. Enzyme-linked immunosorbent assay (ELISA) showed that the seroprevalence was 42.21% for Macaca fascicularis and 43.59% for Macaca nemestrina. Furthermore, the seroprevalence was 53.41% for captive macaques and 17.83% for wild macaques. The findings showed that exposure to B. pseudomallei happened in both captive and wild macaques. Based on this serosurveillance results, further studies such as comprehensive culture and clinical study are required to discover the clinical burden of the disease in nonhuman primates.